The Effect of Company’s Fundamental, Market Return and Macroeconomic to Stock Return: A Case Study of Consumer Goods Companies Listed in BEI Period 2009-2018 - Juliana Thamrin; Roy Sembel (Sekolah Tinggi Manajemen IPMI, 2020)
The aim of this study was to understand whether the company’s fundamental factors through liquidity ratio, asset management ratio, profitability ratio, debt management ratio and market value ratio, specifically represented by current ratio, Total Assets Turnover (TATO), Return on Assets (ROA), Debt to Equity ratio (DER) and Earnings per Share (EPS) yield; market return and macroeconomic factors (Gross Domestic Product, interest rate, exchange rate) affect the stock return of Consumer Goods companies’ listed in BEI period 2009-2018. There were various former studies did to correlate stock return with financial ratios or macroeconomic partially. This study was done to understand the effect of the stock return with both company’s factors and macroeconomic factors, partially and simultaneously. This study used quantitative approach, in the area of Consumer Goods companies listed in BEI during period of the research, covering 23 companies that represented 84% of Consumer Goods market capitalization. The methodology being used was data panel regression using Common Effect Model, through 886 observations. The results were (1) partially, TATO, EPS yield, market return and exchange rate affected the stock return (2) simultaneously company’s fundamental, market return and macroeconomic affected the stock return. This means in consumer sector, investors put attention on asset management, earnings yield, market condition and macroeconomic. Therefore, the author recommended that many extended researches can be done on the financial ratios, market return and macroeconomic, using different variable, especially due to TATO affect the stock return while conversely ROA and DER were not.